Disseminated histoplasmosis and tuberculosis: dual infection in a non-endemic region - Anot, Karuna (BMJ Case Rep, 2020)
Histoplasmosis is a systemic fungal infection caused by Histoplasma capsulatum, a dimorphic fungus that spreads commonly by contamination of soil with bird and bat droppings. The infection remains latent in most patients until manifested by reduced immune status, for example, HIV/AIDS, corticosteroid/immunosuppressive therapy or in solid organ transplant recipients. Tuberculosis and histoplasmosis may cooccur rarely in HIV and the clinical resemblance of both diseases may hinder identification of patients’ harbouring dual infection, especially in regions non-endemic for histoplasmosis. We report a case of disseminated histoplasmosis with disseminated tuberculosis in an incidentally detected patient with HIV-positive who presented with reports of fever and skin rash for 10 days. The Mantoux positivity and CT of chest and abdomen revealing multiple necrotic lymph nodes coupled with bone marrow and skin biopsy divulging histoplasmosis and tuberculosis helped us clinch the concurrent infection.